Composite material beneficial to shielding of electromagnetic interference of engine of unmanned aerial vehicle and preparation method of composite material

By using a five-layer gradient impedance matching structure and a composite material with synergistic functional configuration, the weight and compatibility issues of electromagnetic interference shielding materials for UAV engines have been resolved. This has enabled efficient electromagnetic wave absorption and lightweight design, meeting the integrated requirements of electromagnetic shielding and structural load-bearing for UAVs.

CN121043479AActive Publication Date: 2025-12-02ZHEJIANG SHANGYUN AVIATION TECHNOLOGY CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202511581186.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2025-12-02
Estimated Expiration
2045-10-31

AI Technical Summary

Technical Problem

Existing electromagnetic interference shielding materials for drone engines are heavy, difficult to process, have poor compatibility with composite material airframe structures, and lack effective electromagnetic absorption capabilities, thus failing to meet the requirements of lightweight and integrated design for drones.

Method used

A five-layer gradient impedance matching structure is adopted, including a high permeability absorption layer, an impedance transition layer, a broadband absorption layer, a metal reflection layer, and a carbon fiber reinforced protective layer. Through the synergistic configuration of carbonyl iron powder, manganese zinc ferrite nanoparticles, multi-walled carbon nanotubes, and graphene nanosheets, the magnetic loss and dielectric loss are organically combined, optimizing the absorption and attenuation of electromagnetic waves.

Benefits of technology

It achieves efficient electromagnetic wave absorption in a wide frequency band from 0.1 to 18 GHz, reduces material surface density by 40% to 60%, exhibits excellent mechanical properties and good environmental stability, and meets the compatibility and electromagnetic shielding requirements of UAV airframe structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121043479A_ABST
    Figure CN121043479A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electromagnetic shielding composite materials, in particular to a composite material beneficial to shielding of electromagnetic interference of an engine of an unmanned aerial vehicle and a preparation method thereof.The composite material is of a five-layer structure, the outer layer is a high-permeability absorption layer and is 0.8-1.2 mm thick, the inner layer is an impedance transition layer and is 0.5-0.8 mm thick, and the composite material is composed of polyimide, silicon carbide whiskers and flaky carbonyl iron powder; the broadband absorption layer is arranged inwards, the thickness of the broadband absorption layer ranges from 1.5 mm to 2.5 mm, polyether-ether-ketone serves as a matrix, manganese zinc ferrite, carbon nanotubes and graphene are compounded, the metal reflection layer with the thickness ranging from 0.3 mm to 0.6 mm is arranged on the inner side of the broadband absorption layer, an alloy thin plate with specific roughness is adopted, the carbon fiber reinforced protection layer is arranged on the innermost layer, the thickness of the carbon fiber reinforced protection layer ranges from 0.8 mm to 1.5 mm, and the carbon fiber reinforced protection layer is formed by compounding carbon fibers and epoxy resin and provides structural support; by adjusting the characteristic impedance of the material layer by layer, the step-by-step attenuation of electromagnetic waves is realized, and the interface reflection is minimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electromagnetic shielding composite materials technology, and more specifically, to a composite material and its preparation method that is beneficial for shielding the electromagnetic interference of a drone's own engine. Background Technology

[0002] With the rapid development and widespread application of drone technology, electromagnetic compatibility (EMC) issues in drone systems are becoming increasingly prominent. Drone engines generate strong electromagnetic radiation during operation, and this EMC is mainly concentrated in a wide frequency range of 100 MHz to 18 GHz. This can seriously affect the normal operation of precision electronic equipment such as airborne navigation systems, communication systems, and flight control systems, and may even lead to system failures and safety accidents. While traditional metal shielding materials have good EMC performance, they suffer from problems such as heavy weight, difficult processing, and poor compatibility with composite material airframe structures, making it difficult to meet the demands of modern drones for lightweight and integrated design.

[0003] Chinese patent application publication CN118124213A discloses a wear-resistant, lightweight composite metal material for drone shells. This material consists of a three-layer structure: a carbon fiber matrix layer, an electromagnetic shielding adhesive interlayer, and a metal matrix composite layer. The main purpose of this technical solution is to improve the mechanical properties and wear resistance of the drone shell, with electromagnetic shielding function existing only as an auxiliary feature in the interlayer adhesive. However, this technical solution has the following shortcomings. First, the simple electromagnetic shielding adhesive layer uses a passive reflection shielding mechanism. For high-intensity electromagnetic radiation from the drone's internal engine, this reflective shielding will cause electromagnetic waves to be reflected multiple times within the shell, potentially exacerbating electromagnetic interference. Second, the three-layer structure of this material does not consider the impedance matching relationship between different layers, resulting in significant impedance abrupt changes at the interlayer interfaces. This causes a large number of incident electromagnetic waves to be reflected at the interfaces and cannot be effectively absorbed. Third, the metal matrix composite layer of this material primarily pursues mechanical properties, and its composition design is not optimized for the absorption mechanism of electromagnetic waves, lacking an effective synergistic configuration of magnetic loss phases and dielectric loss phases. Finally, the technical solution does not disclose the shielding effectiveness data and frequency response characteristics of the material in a specific frequency band, making it impossible to assess its actual protection capability against electromagnetic interference from drone engines.

[0004] Currently, there is a lack of systematic research and development on dedicated shielding materials for electromagnetic interference (EMI) from UAV engines. Existing technologies typically employ methods such as bonding absorbing materials inside the airframe or using conductive coatings for EMI protection. However, these methods suffer from problems such as complex construction, poor durability, and added weight. Therefore, there is an urgent need to develop a composite material specifically designed for the EMI characteristics of UAV engines. This material should possess highly efficient electromagnetic absorption capabilities, lightweight yet high-strength mechanical properties, good compatibility with the UAV airframe structure, and reliable environmental stability. Summary of the Invention

[0005] To address the aforementioned shortcomings of existing technologies, the present invention aims to provide a composite material and its preparation method for shielding unmanned aerial vehicles (UAVs) from electromagnetic interference from their own engines. This composite material employs a five-layer gradient impedance matching structure design. Through the synergistic configuration of multiple functional phases, including carbonyl iron powder, manganese-zinc ferrite nanoparticles, multi-walled carbon nanotubes, and graphene nanosheets, it achieves an organic combination of magnetic and dielectric losses, exhibiting excellent absorption and attenuation capabilities for electromagnetic waves in a wide frequency band from 0.1 to 18 GHz. Simultaneously, this composite material maintains lightweight and high-strength mechanical properties, with an areal density of only 3.5 to 5.2 kg / m², reducing weight by 40% to 60% compared to traditional metal shielding materials. It can be directly applied to the manufacture of UAV airframe structures, achieving an integrated design of electromagnetic shielding and structural load-bearing.

[0006] To achieve the above objectives, the present invention provides the following technical solution. The present invention provides a composite material that facilitates shielding of a drone's own engine from electromagnetic interference. This composite material is composed of five layers arranged sequentially from the outside in. The outermost layer is a high-permeability absorbing layer with a thickness of 0.8 to 1.2 mm, composed of an epoxy resin matrix and surface-modified carbonyl iron powder. The mass fraction of the surface-modified carbonyl iron powder is 65% to 75%, and the particle size ranges from 3 to 8 micrometers. As a magnetic loss phase, the carbonyl iron powder exhibits excellent natural ferromagnetic resonance absorption characteristics in the low-frequency band. Its high saturation magnetization and moderate coercivity enable this layer to strongly absorb magnetic field components in the 0.1 to 2 GHz frequency band.

[0007] Adjacent to the inner side of the high-permeability absorption layer is an impedance transition layer, 0.5 to 0.8 mm thick, composed of a polyimide matrix, silicon carbide whiskers, and flake-shaped carbonyl iron powder. The silicon carbide whiskers comprise 15% to 25% by mass and have an aspect ratio of 20 to 50, while the flake-shaped carbonyl iron powder comprises 30% to 40% by mass and has a diameter of 5 to 15 micrometers and a thickness of 0.5 to 1.5 micrometers. This layer is designed to achieve impedance gradient matching between the high-permeability absorption layer and the broadband absorption layer. The high imaginary part of the dielectric constant of the silicon carbide whiskers provides excellent dielectric loss capability, while the anisotropic shape of the flake-shaped carbonyl iron powder enhances the magnetic loss effect. The combination of these two elements results in a characteristic impedance between the first and third layers, effectively reducing interface reflection loss.

[0008] Located inside the impedance transition layer is a broadband absorption layer, the core functional layer of the composite material. This layer, 1.5 to 2.5 mm thick, consists of a polyetheretherketone (PEEK) matrix, manganese-zinc ferrite nanoparticles, multi-walled carbon nanotubes, and graphene nanosheets. The manganese-zinc ferrite nanoparticles comprise 25% to 35% of the composite material by mass, with an average particle size of 30 to 80 nm. This component exhibits excellent synergistic effects in magnetic and dielectric losses in the 2 to 18 GHz high-frequency range. The multi-walled carbon nanotubes comprise 3% to 8% of the composite material by mass, with an outer diameter of 10 to 30 nm and a length of 5 to 20 μm. Their high aspect ratio structure forms a conductive network within the matrix, providing dipole polarization and interfacial polarization losses. The graphene nanosheets comprise 1% to 3% of the composite material by mass, with a sheet diameter of 1 to 5 μm and a thickness of 3 to 10 nm. Their two-dimensional structure and high conductivity further enhance the dielectric loss capability. The synergistic effect of these three functional phases enables this layer to achieve efficient absorption and conversion of electromagnetic wave energy in the mid-to-high frequency range.

[0009] The inner side of the broadband absorption layer is a metallic reflective layer, 0.3 to 0.6 mm thick, made of aluminum or copper alloy sheet with a surface roughness controlled between 0.4 and 0.8 micrometers. The main function of this layer is to reflect residual transmitted electromagnetic waves, creating a secondary absorption effect, while simultaneously enhancing the overall mechanical strength and thermal stability of the composite material.

[0010] The innermost layer is a carbon fiber reinforced protective layer, which is 0.8 to 1.5 mm thick and is composed of carbon fiber woven fabric and epoxy resin, with the carbon fiber volume fraction being 55% to 65%. This layer not only provides the necessary mechanical strength and impact resistance, but the conductivity of the carbon fiber itself also creates an additional electromagnetic shielding effect, further reducing the transmittance of electromagnetic waves.

[0011] In a preferred embodiment, the surface-modified carbonyl iron powder in the high magnetic permeability absorption layer is obtained through surface modification treatment with a silane coupling agent. Specifically, the carbonyl iron powder is vacuum dried at 80 to 100 degrees Celsius for 2 hours to remove surface adsorbed water, then dispersed in anhydrous ethanol, and 3% to 5% (by mass) of γ-aminopropyltriethoxysilane coupling agent is added. The mixture is then mechanically stirred at 60 to 70 degrees Celsius for 4 to 6 hours. During this process, silane molecules undergo hydrolysis and condensation reactions on the iron powder surface to form a coating layer. The amino groups in the silane molecules can undergo ring-opening reactions with the epoxy resin, achieving chemical bonding between the iron powder and the matrix. After the reaction is complete, the powder is centrifuged, washed three times with anhydrous ethanol, and vacuum dried at 80 degrees Celsius for 4 hours to obtain the surface-modified carbonyl iron powder. This surface modification treatment significantly improves the dispersion stability of the carbonyl iron powder in the organic matrix, reduces agglomeration, and thus improves the electromagnetic uniformity and mechanical properties of the composite material.

[0012] In another preferred embodiment, the manganese-zinc ferrite nanoparticles in the broadband absorption layer are prepared by a sol-gel method. Manganese nitrate, zinc nitrate, and ferric nitrate are dissolved in deionized water in stoichiometric proportions to prepare a mixed solution with a total metal ion concentration of 0.5 to 0.8 mol / L, wherein the molar ratio of manganese, zinc, and iron is 0.4 to 0.6:0.2 to 0.4:1.8 to 2.2. Sodium hydroxide solution is added dropwise to the mixed solution under vigorous stirring to adjust the pH to 10.5 to 11.5, causing a co-precipitation reaction of the metal ions to form a precursor gel. The gel is aged at 80 to 90 degrees Celsius for 12 to 18 hours, during which the internal structure of the gel gradually stabilizes and forms a uniform metal hydroxide network. Subsequently, it is repeatedly washed with deionized water until neutral and dried at 100 degrees Celsius for 8 hours to obtain the precursor powder. Precursor powder was heated to 800-900°C in a muffle furnace at a heating rate of 5°C per minute and held for 2-4 hours for high-temperature sintering. At this temperature, the precursor underwent dehydration and crystallization reactions to form spinel-structured manganese-zinc ferrite. Precise control of the sintering temperature is crucial for obtaining pure phase and ferrite nanoparticles of the desired particle size; too low a temperature leads to incomplete crystallization, while too high a temperature results in excessive particle growth. The nanoparticles were then cooled to room temperature in the furnace to obtain manganese-zinc ferrite nanoparticles. The manganese-zinc ferrite nanoparticles prepared by this method exhibit high saturation magnetization and moderate coercivity, demonstrating excellent imaginary part of complex permeability and magnetic loss capacity in the 2-18 GHz frequency band.

[0013] More preferably, the multi-walled carbon nanotubes in the broadband absorption layer undergo a dual functionalization modification treatment of acidification and grafting. First, the multi-walled carbon nanotubes are refluxed at 80°C for 6 to 8 hours in a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, with a volume ratio of concentrated sulfuric acid to concentrated nitric acid of 3:1. Under the oxidizing effect of the strong acid, some carbon atoms on the surface of the carbon nanotubes are oxidized, introducing oxygen-containing functional groups such as carboxyl and hydroxyl groups. Simultaneously, some cap structures are destroyed, and defects in the nanotube walls increase. These oxygen-containing functional groups not only improve the hydrophilicity and dispersibility of the carbon nanotubes but also provide reaction sites for subsequent chemical grafting. The treated carbon nanotubes are repeatedly washed with deionized water until neutral and then vacuum-dried overnight at 80°C. Then, the acidified carbon nanotubes are dispersed in N,N-dimethylformamide, and an excess of thionyl chloride is added, followed by reflux at 70 to 80°C for 12 hours. The thionyl chloride reacts with the carboxyl groups on the surface of the carbon nanotubes, converting them into more reactive acyl chloride groups. After filtering to remove excess thionyl chloride, the product was redispersed in N,N-dimethylformamide, and aminopropyltriethoxysilane was added. The mixture was reacted at 60°C for 24 hours. The aminopropyl group underwent a nucleophilic substitution reaction with the acyl chloride group to form a stable amide bond, thereby achieving the grafting of silane molecules onto the surface of carbon nanotubes. The triethoxysilane end group in the silane molecule can interact with the polyether ether ketone matrix, enhancing the interfacial bonding. The final product was subjected to Soxhlet extraction to remove unreacted reagents and vacuum dried at 80°C for 12 hours to obtain functionalized multi-walled carbon nanotubes. This dual functionalization modification significantly improved the dispersibility of carbon nanotubes in the polymer matrix and enhanced interfacial interactions through chemical bonding, thereby improving the dielectric loss capacity and mechanical properties of the composite material.

[0014] Preferably, the graphene nanosheets in the broadband absorption layer are obtained by preparing graphene oxide via a modified Hummers method followed by chemical reduction. Natural flake graphite powder is mixed with concentrated sulfuric acid, and potassium permanganate is slowly added under ice bath conditions. The reaction temperature is strictly controlled to not exceed 20 degrees Celsius during the addition process to avoid excessive destruction of the graphite structure due to a vigorous oxidation reaction. Under the strong oxidizing effect of potassium permanganate, the graphite layers are intercalated and oxidized to form graphene oxide. The temperature is then raised to 35-40 degrees Celsius for 2 hours to promote a complete oxidation reaction. Deionized water is added for dilution, and the temperature is raised to 95 degrees Celsius for 30 minutes. During this process, the expansion and exfoliation between the graphene oxide layers intensify. Finally, hydrogen peroxide is added to terminate the reaction; the solution color changes from brown to bright yellow, indicating that the permanganate ions have been reduced. The reaction product is centrifuged and repeatedly washed with deionized water until neutral to obtain a graphene oxide dispersion. Although graphene oxide has good hydrophilicity and dispersibility, its conductivity is poor, requiring reduction treatment to restore the conjugated structure of graphene. A dispersion of graphene oxide was mixed with hydrazine hydrate at a mass ratio of 1:10. Ammonia was added to adjust the pH to 10 to provide an alkaline environment to promote the reduction reaction. The mixture was refluxed at 95°C for 24 hours. The hydrazine hydrate, acting as a reducing agent, removed oxygen-containing functional groups from the surface of the graphene oxide, significantly improving the material's conductivity. The reduction product was centrifuged, washed with deionized water, and freeze-dried to obtain graphene nanosheets. The freeze-drying process effectively prevented the graphene sheets from re-stacking, maintaining their high specific surface area. The resulting graphene nanosheets possessed a high specific surface area and excellent conductivity, forming a highly efficient conductive network in the composite material and significantly enhancing dielectric loss capacity.

[0015] This invention also provides a method for preparing the above-mentioned composite material, which includes the following steps. The first step is to prepare a high magnetic permeability absorbing layer. Surface-modified carbonyl iron powder is added to epoxy resin at a mass fraction of 70%, preferably E-51 epoxy resin with an epoxy value of 0.48 to 0.54 mol per 100g. The mixture is dispersed for 30 minutes using a high-shear disperser at a speed of 2000 to 2500 rpm. The strong shear force generated by the high shear action effectively breaks down the agglomerates of carbonyl iron powder, allowing it to be uniformly dispersed in the resin. Then, a polyamide curing agent at a mass fraction of 30% to 35% of the epoxy resin is added and stirring is continued for 10 minutes. The active hydrogen in the polyamide curing agent can undergo a ring-opening addition reaction with the epoxy groups, initiating cross-linking and curing of the epoxy resin. The mixture is then vacuum degassed for 20 minutes under a vacuum degree of -0.08 to -0.09 MPa to remove air bubbles introduced during the mixing process. The presence of air bubbles reduces the mechanical and electromagnetic properties of the composite material. The degassed mixture was poured into a stainless steel mold pre-coated with a release agent, and the thickness was controlled to be 1.0 mm. A programmed curing process was then performed: pre-curing at 60°C for 2 hours to allow the resin system to reach a preliminary gel state, curing at 120°C for 4 hours to ensure sufficient cross-linking reaction, and finally post-curing at 150°C for 2 hours to improve cross-linking density and heat resistance. After cooling to room temperature in the oven, the mixture was demolded to obtain a high magnetic permeability absorbing layer substrate.

[0016] The second step is to prepare the impedance transition layer. Polyimide powder is dissolved in N-methylpyrrolidone solvent to prepare a polyimide solution with a solid content of 15% to 20%, preferably PI-2611. Silicon carbide whiskers and flake carbonyl iron powder are added to the polyimide solution according to the designed mass fraction, and dispersed for 1 hour using a combination of ultrasonic dispersion and mechanical stirring. The ultrasonic dispersion uses an ultrasonic power of 500 watts and an ultrasonic frequency of 20 kHz. The microjets and shock waves generated by ultrasonic cavitation effectively disperse the filler and break up agglomerates, while mechanical stirring ensures the macroscopic uniformity of the dispersion. The uniformly dispersed mixture is coated onto the surface of the high permeability absorption layer substrate obtained in the first step using a scraping method, controlling the wet film thickness to 3 to 4 mm. Pre-baking at 80 degrees Celsius for 2 hours removes most of the solvent, followed by programmed temperature treatment in a vacuum oven. Initially, it is held at 120 degrees Celsius for 2 hours to further remove the solvent and initiate the imidization reaction of the polyamic acid precursor. The imidization reaction was then carried out at 180°C for 2 hours. Next, it was maintained at 250°C for 1 hour, during which most of the polyamic acid was converted to polyimide. Finally, imidization was performed at 320°C for 4 hours to ensure complete conversion of the polyamic acid to polyimide and the formation of a highly cross-linked network structure. The heating rate during the programmed heat treatment was strictly controlled at 2 to 3°C per minute. This slow heating rate prevented rapid evaporation of solvents and reaction byproducts, which could lead to bubbles and defects in the coating, while also ensuring good interfacial bonding between the two layers.

[0017] The third step is to prepare a broadband absorption layer. Polyetheretherketone (PEEK) powder is dissolved in concentrated sulfuric acid to prepare a PEEK solution with a mass fraction of 8% to 12%. The average molecular weight of the PEEK powder is 25,000 to 30,000. Concentrated sulfuric acid is one of the good solvents for PEEK, allowing it to dissolve fully and form a homogeneous solution. Functionalized multi-walled carbon nanotubes and graphene nanosheets are pre-dispersed in N,N-dimethylformamide and ultrasonically treated for 2 hours to obtain a stable dispersion. Ultrasonic treatment can effectively exfoliate the aggregates of carbon nanotubes and graphene. Manganese-zinc ferrite nanoparticles are surface-treated with γ-glycidyl etheroxypropyltrimethoxysilane coupling agent, similar to the surface modification of carbonyl iron powder, and then dispersed in N,N-dimethylformamide. The three dispersions are mixed according to the designed ratio and slowly added to the PEEK solution under mechanical stirring. The addition rate is controlled at 5 to 10 ml per minute to avoid local precipitation of PEEK. After mixing, the mixture was dispersed in a high-speed shear disperser at 3000 rpm for 45 minutes to ensure uniform dispersion of each functional phase in the polyetheretherketone (PEEK) matrix. The uniformly dispersed mixture was then cast onto the surface of the impedance transition layer obtained in the second step, with a thickness controlled at 2.0 mm. It was then pre-baked at 80°C for 1 hour to initially remove the solvent, dried in a vacuum oven at 120°C for 6 hours to further remove the solvent, and treated at 180°C for 4 hours to allow the PEEK to begin melting. Finally, it was hot-pressed at 280°C using a programmed pressure method: first, a pressure of 5 MPa was maintained for 5 minutes to initially compact the material, then the pressure was increased to 10-15 MPa and maintained for 30 minutes. The hot-pressing process allowed the PEEK to fully melt and impregnate each filler phase, expelling residual bubbles under pressure and forming a dense composite structure. This also promoted interfacial fusion between this layer and the impedance transition layer.

[0018] The fourth step is the composite metal reflective layer. A 0.5 mm thick aluminum alloy sheet is used, with a grade of 5052 and a tensile strength of not less than 230 MPa. The surface of the aluminum alloy sheet undergoes chemical pretreatment to improve adhesion strength. First, it is immersed in an alkaline degreasing solution at 60°C for 15 minutes to remove surface oil. The main components of the alkaline degreasing solution are an aqueous solution of sodium hydroxide and sodium silicate. Then, it is acid-washed in a 10% sulfuric acid solution at room temperature for 5 minutes to activate the surface, remove the oxide film, and increase surface activity. Finally, it undergoes chemical oxidation treatment for 10 minutes in a chromic acid-phosphoric acid mixture to form a micron-level roughened surface. The mass ratio of chromic acid to phosphoric acid in the chromic acid-phosphoric acid mixture is 2:1. This chemical oxidation treatment creates a micron-level rough structure on the aluminum sheet surface, significantly increasing the surface area and mechanical anchoring points, thereby improving adhesion strength. The treated aluminum sheet is then thoroughly rinsed with deionized water and dried. The two-component epoxy structural adhesive is thoroughly mixed, with a main component to curing agent mass ratio of 100:30. It is then uniformly applied to the aluminum plate surface using a scraper coating method, with the coating thickness controlled between 0.15 and 0.20 mm. Subsequent operations must be completed within 30 minutes after application to ensure the adhesive layer's flowability and wetting effect. The coated aluminum plate is then bonded to the surface of the broadband absorbing layer obtained in step three and rolled in a roller press at a pressure of 0.5 MPa. Rolling removes air bubbles and ensures uniform contact and thorough wetting between the two layers. Pre-curing at 60°C for 4 hours allows the structural adhesive to initially cure, followed by curing at 120°C for 6 hours to ensure full cross-linking. The shear strength of the cured bond interface is not less than 18 MPa, ensuring a reliable bond between the metal reflective layer and the broadband absorbing layer.

[0019] The fifth step is to prepare the carbon fiber reinforced protective layer. This is done using a vacuum-assisted resin transfer molding process. A plain-weave carbon fiber fabric with a specification of 3K and an areal density of 200 g / m² is selected. After cutting the plain-weave fabric to the required size, 3 to 4 layers are laid on the surface of the metal reflective layer obtained in the fourth step. An epoxy resin system is prepared, comprising 100 parts epoxy resin, 10 to 15 parts low-viscosity reactive diluent, 30 parts polyamide curing agent, and 0.5 parts defoamer. The addition of the reactive diluent reduces the viscosity of the resin system, facilitating the full impregnation of the carbon fiber fabric under vacuum. The composite material is placed in a vacuum bag, and the resin system is introduced through the designated resin inlet and vacuum outlet at a vacuum level of -0.09 to -0.095 MPa. Under vacuum, the resin gradually impregnates the carbon fiber fabric from the inlet end and flows towards the vacuum outlet end, fully filling the gaps between the fiber bundles. After resin infusion, the resin is initially gelled at 60°C for 2 hours, then cured at 120°C for 4 hours, and finally cured at 150°C for 2 hours. This process ensures a high volume fraction and low porosity of carbon fibers, resulting in a composite material with a porosity of less than 2%, thus achieving excellent mechanical properties.

[0020] The sixth step is the post-processing of the overall composite material. The prepared five-layer composite material is edge-trimmed on a CNC milling machine to ensure dimensional accuracy and edge smoothness, removing any burrs and irregular edges that may have occurred during the preparation process. Then, a stress relaxation treatment is performed at 150 degrees Celsius for 4 hours to eliminate internal stress caused by differences in thermal expansion coefficients and curing shrinkage during preparation, improving the dimensional stability of the composite material. Finally, a 50-80 micrometer thick polyurethane protective coating is sprayed onto the surface of the composite material to provide additional moisture and weather resistance, extending the service life of the composite material.

[0021] The composite material of this invention has the following beneficial effects. First, the composite material adopts a five-layer gradient impedance matching structure design. By adjusting the characteristic impedance of the material layer by layer, the electromagnetic wave is attenuated step by step and the interface reflection is minimized. Theoretically, when electromagnetic waves propagate from one medium to another, if the characteristic impedances of the two media differ significantly, significant reflection loss will occur at the interface, causing a large amount of electromagnetic wave energy to be reflected and unable to enter the material interior for absorption. This invention sets an impedance transition layer between a high-permeability absorption layer and a broadband absorption layer, designing the characteristic impedance of this layer to be the geometric average of the characteristic impedances of the first and third layers. According to impedance matching theory, this gradient design minimizes the interface reflection coefficient, thereby allowing more electromagnetic wave energy to enter the material interior for step-by-step absorption. Experimental results show that compared to a three-layer structure without an impedance transition layer, the five-layer gradient structure of this invention increases the effective absorption bandwidth of the material by 60% to 80%, and improves the average shielding effectiveness by 15 to 25 dB across the entire frequency band from 0.1 to 18 GHz.

[0022] Secondly, this composite material achieves an organic combination of magnetic and dielectric losses through the synergistic configuration of multiple functional phases, including carbonyl iron powder, manganese-zinc ferrite nanoparticles, multi-walled carbon nanotubes, and graphene nanosheets. Electromagnetic wave attenuation mechanisms mainly include magnetic and dielectric losses. Magnetic loss originates from processes such as hysteresis loss, domain wall resonance, and natural ferromagnetic resonance of magnetic materials under alternating magnetic fields, while dielectric loss originates from processes such as dipole polarization of polar molecules, interface polarization of conductive networks, and electronic polarization. A single magnetic or dielectric loss mechanism often only functions within a specific frequency band, making it difficult to achieve efficient absorption across a wide frequency range. This invention introduces functional phases with different electromagnetic response characteristics into different layers, enabling the material to exhibit good electromagnetic wave attenuation capabilities throughout the entire test frequency band. Specifically, the carbonyl iron powder in the high permeability absorption layer plays a major role in the low-frequency range of 0.1 to 2 GHz, and its natural ferromagnetic resonance frequency happens to fall within this band, giving the material high imaginary permeability and strong magnetic loss capabilities in this frequency range. The manganese-zinc ferrite nanoparticles in the broadband absorption layer exhibit excellent synergistic effects of magnetic and dielectric losses in the mid-frequency range of 2–8 GHz. Their nanoscale effect enhances magnetocrystalline anisotropy and surface effects, shifting the magnetic loss peak to higher frequencies. The conductive network formed by multi-walled carbon nanotubes in the 5–15 GHz frequency range generates strong interfacial polarization and dipole polarization losses. The conductive network and two-dimensional structure of graphene nanosheets in the 8–18 GHz high-frequency range further increase the imaginary part of the dielectric constant, transforming the shielding mechanism into one dominated by dielectric loss. This synergistic effect of multiple loss mechanisms enables the material to maintain continuous and efficient absorption of electromagnetic waves in the 0.1–18 GHz broadband frequency range.

[0023] Furthermore, this composite material achieves uniform dispersion and interfacial chemical bonding of the nano-absorbing phase within the polymer matrix through surface functionalization and controllable synthesis techniques. Nanoparticles, due to their high specific surface area and high surface energy, are prone to agglomeration in polymer matrices, which significantly reduces the electromagnetic and mechanical properties of the material. This invention modifies the surface of carbonyl iron powder, carbon nanotubes, and manganese-zinc ferrite nanoparticles with a silane coupling agent, introducing organic functional groups onto the nanoparticle surface. These organic functional groups can, on the one hand, reduce the surface energy of the particles and provide steric hindrance to prevent agglomeration; on the other hand, they can react chemically with the polymer matrix to form interfacial chemical bonds, significantly enhancing the interfacial bonding force. The acidification-grafting dual functionalization modification of carbon nanotubes introduces carboxyl groups onto the carbon nanotube surface, which are then further converted into acyl chloride groups that react with silane molecules, achieving a strong grafting of silane molecules onto the carbon nanotube surface via amide bonds. The chemical reduction process of graphene removes oxygen-containing functional groups, restoring conductivity, while also retaining a small number of hydroxyl and carboxyl groups to provide reaction sites for subsequent functionalization. These surface functionalization treatments improve the dispersion stability of the nano-absorbing phase in the polymer matrix by an order of magnitude, increase the retention rate of electromagnetic properties of the material in harsh environments by 20% to 30%, and significantly enhance the mechanical properties and durability of the composite material through improved interfacial chemical bonding.

[0024] Furthermore, this composite material achieves excellent electromagnetic shielding performance while maintaining lightweight and high-strength mechanical properties. The areal density of the composite material is only 3.5 to 5.2 kg / m², a 40% to 60% reduction compared to the areal density of traditional metal shielding materials (8 to 12 kg / m²). This significant weight reduction is crucial for drone applications, directly reducing the drone's fuselage weight, increasing payload, or extending flight time. Simultaneously, the composite material exhibits tensile strength of 185 to 230 MPa, flexural strength of 280 to 350 MPa, interlaminar shear strength of 35 to 45 MPa, and impact strength of 45 to 60 kJ / m². These mechanical properties meet or even exceed the load-bearing requirements of drone fuselage structures. The introduction of a carbon fiber reinforced protective layer not only provides excellent mechanical properties, but the conductivity of the carbon fiber itself also forms an additional electromagnetic shielding layer, further enhancing the overall shielding effectiveness of the material. The presence of a metal reflective layer enhances the stiffness and thermal stability of the composite material, enabling it to maintain good dimensional stability and electromagnetic properties even at high temperatures.

[0025] Finally, the composite material exhibits excellent environmental stability and durability. During actual use, drones are subjected to various environmental factors such as temperature, humidity, ultraviolet radiation, and salt spray corrosion. Electromagnetic shielding materials must maintain stable performance under these harsh conditions. This invention utilizes polyetheretherketone (PEEK) and polyimide, both with excellent weather resistance, as matrix materials, and applies a polyurethane protective coating to the surface, resulting in a composite material with superior environmental stability. PEEK possesses a high glass transition temperature and excellent chemical corrosion resistance, while polyimide exhibits outstanding high-temperature stability and mechanical strength. After 1000 hours of accelerated aging testing in a constant temperature and humidity chamber at 85°C and 85% relative humidity, the material's electromagnetic shielding effectiveness decreased by less than 8%, its mass increased by less than 1.5%, and no significant corrosion or cracking was observed on the surface. In the salt spray corrosion test, after 500 hours of continuous spraying of a 5% sodium chloride solution at 35°C, the carbon fiber protective layer and polyurethane coating on the material surface effectively prevented the penetration of corrosive media, and the internal metal reflective layer and absorbing phase showed no significant corrosion, with a shielding effectiveness decrease of less than 5%. These environmental stability test results show that the composite material of the present invention can work stably for a long time in various harsh environments, meeting the stringent requirements of unmanned aerial vehicle systems for the reliability and durability of electromagnetic shielding materials. Attached Figure Description

[0026] Figure 1 This is a schematic diagram of the layered structure of the composite material of the present invention, wherein 1 is a high permeability absorption layer, 2 is an impedance transition layer, 3 is a broadband absorption layer, 4 is a metal reflective layer, and 5 is a carbon fiber reinforced protective layer.

[0027] Figure 2 This is a graph showing the electromagnetic shielding effectiveness of the composite material of the present invention in the frequency band from 0.1 to 18 GHz.

[0028] Figure 3 This is a comparison chart of the shielding effectiveness of the composite materials prepared in Examples 1 to 6 of the present invention.

[0029] Figure 4 This is a comparative diagram showing the shielding effectiveness and mechanical properties of the embodiments and comparative examples of the present invention. Detailed Implementation

[0030] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments thereof. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0031] Unless otherwise specified, all raw materials used in the embodiments of this invention can be purchased from the market or prepared by conventional methods. Specifically, the epoxy value of epoxy resin E-51 is 0.51 mol per 100 grams. The polyamide curing agent is type 650 polyamide curing agent. Carbonyl iron powder is purchased from BASF, model CIP-HQ, with an average particle size of 5 μm and a purity of 99.5%. The flake carbonyl iron powder has an average flake diameter of 10 μm and a thickness of 1 μm. The silicon carbide whiskers have an average diameter of 0.8 μm and an average length of 30 μm. Polyimide powder PI-2611 is purchased from DuPont. Manganese nitrate hexahydrate, zinc nitrate hexahydrate, and iron nitrate nonahydrate are all analytical grade and purchased from Sinopharm Chemical Reagent Co., Ltd. Multi-walled carbon nanotubes have a purity greater than 95%, an average outer diameter of 20 nm, and an average length of 10 μm. The natural flake graphite powder has a particle size of 300 mesh. The polyetheretherketone (PEEK) powder, grade PEEK-450G, has an average molecular weight of 27,000. γ-aminopropyltriethoxysilane coupling agent and γ-glycidoxypropyltrimethoxysilane coupling agent were purchased from Sinopharm Chemical Reagent Co., Ltd. The aluminum alloy sheet (5052) has a thickness of 0.5 mm and a tensile strength of 235 MPa. The carbon fiber plain weave fabric, grade 3K, with an areal density of 200 g / m², was purchased from Weihai Guangwei Composite Materials Co., Ltd. The two-component epoxy structural adhesive is model HN-7665. The polyurethane protective coating was purchased from Guangzhou Xiupo Chemical Co., Ltd.

[0032] Example 1 This embodiment prepares a composite material that helps UAVs shield themselves from electromagnetic interference from their engines. The composite material adopts a five-layer gradient structure design.

[0033] First, surface-modified carbonyl iron powder was prepared. 200 g of carbonyl iron powder was weighed and placed in an oven, where it was vacuum-dried at 90°C for 2 hours, with the vacuum level controlled at -0.08 MPa. After drying, the carbonyl iron powder was transferred to a three-necked flask containing 500 mL of anhydrous ethanol and dispersed thoroughly under mechanical stirring. 8 g of γ-aminopropyltriethoxysilane coupling agent, equivalent to 4% of the mass of the carbonyl iron powder, was weighed and slowly added dropwise to the dispersion. The three-necked flask was placed in a constant-temperature water bath and heated to 65°C, where it was mechanically stirred for 5 hours. During the reaction, the silane coupling agent molecules first hydrolyzed under the action of ethanol, generating silanol groups. These silanol groups then underwent a condensation reaction with the hydroxyl groups on the surface of the carbonyl iron powder, forming a siloxane coating layer on the iron powder surface. Simultaneously, the amino groups in the silane molecules extended into the solution, providing active sites for subsequent reactions with epoxy resin. After the reaction was complete, heating was stopped, and the mixture was transferred to a centrifuge and centrifuged at 8000 rpm for 10 minutes. The supernatant was discarded, and 300 mL of anhydrous ethanol was added to the precipitate. After ultrasonic dispersion, the mixture was centrifuged again. This washing process was repeated three times to remove unreacted silane coupling agent and reaction byproducts. The final precipitate was transferred to a vacuum drying oven and dried at 80°C and -0.09 MPa for 4 hours to obtain surface-modified carbonyl iron powder.

[0034] Next, a high-permeability absorption layer was prepared. 140 g of surface-modified carbonyl iron powder and 60 g of epoxy resin E-51 were weighed and premixed in a planetary mixer for 10 minutes. The mixture was then transferred to a high-shear disperser and dispersed at 2200 rpm for 30 minutes. The strong shear force generated during high-shear dispersion effectively broke up the agglomerates of carbonyl iron powder, achieving nanoscale dispersion in the epoxy resin. After dispersion, 19.5 g of polyamide curing agent (equivalent to 32.5% of the epoxy resin mass) was weighed and added to the mixture. The mixture was manually stirred for 10 minutes to ensure thorough mixing. The mixture was then transferred to a vacuum degassing device and evacuated for 20 minutes at a vacuum level of -0.085 MPa. A large number of bubbles were observed escaping from the mixture, and after degassing, the mixture became clear and transparent. A layer of silicone oil release agent was uniformly coated onto the inner surface of a stainless steel mold. The degassed mixture was then slowly poured into the mold, and the surface was smoothed with a scraper, controlling the thickness to 1.0 mm. The mold was placed in a programmed oven for curing. First, it was held at 60°C for 2 hours, during which the epoxy resin began to react with the curing agent and reached a preliminary gel state. Then, the temperature was raised to 120°C and held for 4 hours, during which the cross-linking reaction accelerated, and the resin system formed a three-dimensional network structure. Finally, the temperature was raised to 150°C and held for 2 hours for post-curing, which further increased the cross-linking density and eliminated residual stress. After curing, the mold was cooled to room temperature in the oven and removed from the mold, yielding a high-permeability absorbing layer substrate. Its actual thickness was measured to be 1.0 mm, and the surface was smooth and free of bubbles and cracks.

[0035] Then, the dispersion required for the impedance transition layer was prepared. 10 grams of polyimide powder PI-2611 was weighed and added to 50 ml of N-methylpyrrolidone solvent. The mixture was mechanically stirred at 80°C for 2 hours to ensure complete dissolution, resulting in a polyimide solution with a solid content of 16.7%. 2 grams of silicon carbide whiskers and 4 grams of flake carbonyl iron powder were weighed and added to 30 ml of the polyimide solution, according to the design ratio of 20% silicon carbide whiskers and 40% flake carbonyl iron powder in this example. This equates to 5 grams of solid polyimide. Ultrasonic dispersion was performed using an ultrasonic disperser with an ultrasonic power set to 500 watts and an ultrasonic frequency of 20 kHz for 30 minutes. The cavitation effect of ultrasound generated an instantaneous high-temperature, high-pressure microenvironment and strong microjets, effectively breaking up the agglomerates of silicon carbide whiskers and flake carbonyl iron powder. After ultrasonic treatment, the mixture was stirred on a mechanical stirrer for another 30 minutes to ensure the macroscopic uniformity of the dispersion. The dispersion was examined using an optical microscope, confirming the absence of agglomerates larger than 50 micrometers. The uniformly dispersed mixture was then coated onto the surface of a high-permeability absorption layer substrate using a four-sided doctor blade with a gap of 3.5 mm to control the wet film thickness. After coating, the sample was pre-baked in an oven at 80°C for 2 hours, during which most of the N-methylpyrrolidone solvent evaporated. The sample was then transferred to a vacuum oven for programmed heat treatment. First, it was held at 120°C for 2 hours, at which point the polyamic acid precursor began to lose water and undergo intramolecular cyclization to transform into polyimide. The temperature was then raised to 180°C and held for 2 hours, further initiating the imidization reaction. Next, the temperature was raised to 250°C and held for 1 hour, after which most of the polyamic acid had been converted into polyimide. Finally, the temperature was raised to 320°C and held for 4 hours for complete imidization, ensuring the complete conversion of polyamic acid into polyimide and the formation of a highly cross-linked network structure. The entire heating process was strictly controlled at a heating rate of 2.5 degrees Celsius per minute. Slow heating avoids rapid evaporation of solvents and reaction byproducts, which could lead to coating defects. After heat treatment, the impedance transition layer and the high permeability absorption layer were firmly bonded together, and the actual thickness of the impedance transition layer was measured to be 0.65 mm.

[0036] Next, the functionalized filler required for the broadband absorption layer was prepared. First, manganese-zinc ferrite nanoparticles were prepared. 14.35 g of manganese nitrate hexahydrate, 3.57 g of zinc nitrate hexahydrate, and 36.36 g of ferric nitrate nonahydrate were weighed out in a molar ratio of 0.5:0.3:2.0 and dissolved in 200 mL of deionized water to prepare a mixed solution with a total metal ion concentration of 0.6 mol / L. The solution was placed on a thermostatic magnetic stirrer, and under vigorous stirring, a 2 mol / L sodium hydroxide solution was added dropwise using a dropping funnel, while simultaneously monitoring the pH value of the solution with a pH meter. When the pH value reached 11.0, the addition of sodium hydroxide solution was stopped. At this point, the solution color changed from clear to dark brown, indicating that the metal ions had undergone a co-precipitation reaction to form a metal hydroxide gel. The gel was aged at 85°C for 15 hours, during which the internal structure of the gel gradually stabilized. After aging, the gel was repeatedly washed with deionized water until the pH of the supernatant was neutral, and then dried in a 100°C oven for 8 hours to obtain a brown precursor powder. The precursor powder was ground into a fine powder and placed in an alumina crucible, which was then placed in a muffle furnace. The muffle furnace was programmed to heat from room temperature to 850°C at a rate of 5°C per minute, and held at 850°C for 3 hours for high-temperature sintering. During sintering, the precursor powder underwent dehydration and crystallization reactions, and the brown powder gradually turned black, forming a spinel-structured manganese-zinc ferrite. After sintering, the muffle furnace power was turned off, and the sample was allowed to cool slowly to room temperature with the furnace. Slow cooling avoids grain cracking caused by rapid cooling. The sintered powder was removed, thoroughly ground in an agate mortar, and passed through a 200-mesh sieve to obtain manganese-zinc ferrite nanoparticles.

[0037] Then, the manganese-zinc ferrite nanoparticles were surface modified. 30 g of manganese-zinc ferrite nanoparticles were weighed and placed in a three-necked flask, and 150 mL of anhydrous ethanol was added to disperse them. 1.2 g of γ-glycidyl etheroxypropyltrimethoxysilane coupling agent, equivalent to 4% of the ferrite mass, was weighed and added dropwise to the dispersion. The mixture was mechanically stirred at 65°C for 5 hours to allow the silane coupling agent to undergo hydrolysis and condensation reactions on the surface of the ferrite particles, forming a coating layer. After the reaction was complete, the nanoparticles were centrifuged and washed three times with anhydrous ethanol, then vacuum dried at 80°C for 4 hours to obtain the surface-modified manganese-zinc ferrite nanoparticles.

[0038] Next, functionalized multi-walled carbon nanotubes were prepared. 5 grams of multi-walled carbon nanotubes were weighed and added to a mixed acid solution consisting of 90 mL of concentrated sulfuric acid and 30 mL of concentrated nitric acid (volume ratio 3:1). The mixture was placed in a three-necked flask and refluxed at 80°C for 7 hours. During reflux, some carbon atoms on the surface of the carbon nanotubes were oxidized by the strong acid, introducing oxygen-containing functional groups such as carboxyl and hydroxyl groups. After treatment, the mixture was slowly poured into a large amount of ice water to quench the reaction, and then the carbon nanotubes were separated by vacuum filtration. The filtrate was repeatedly washed with deionized water until the pH was neutral, and then dried overnight in a vacuum oven at 80°C to obtain acidified carbon nanotubes. 3 grams of acidified carbon nanotubes were weighed and dispersed in 80 mL of N,N-dimethylformamide, and 20 mL of excess thionyl chloride was added. The mixture was refluxed at 75°C for 12 hours. The thionyl chloride reacted with the carboxyl groups on the surface of the carbon nanotubes to generate acyl chloride groups, and hydrogen chloride and sulfur dioxide gases were released during the reaction. After the reaction was complete, the carbon nanotubes were separated by filtration and washed multiple times with anhydrous N,N-dimethylformamide to remove excess thionyl chloride. The obtained acyl chloride carbon nanotubes were redispersed in 60 mL of N,N-dimethylformamide, and 5 mL of aminopropyltriethoxysilane was added. The reaction was carried out at 60°C for 24 hours. The aminopropyl group and the acyl chloride group underwent a nucleophilic substitution reaction to form an amide bond, achieving a firm grafting of silane molecules onto the surface of the carbon nanotubes. After the reaction was complete, the nanotubes were extracted with N,N-dimethylformamide as a solvent using a Soxhlet extractor for 48 hours to remove unreacted reagents and small molecule byproducts. Finally, the nanotubes were dried in a vacuum oven at 80°C for 12 hours to obtain functionalized multi-walled carbon nanotubes.

[0039] Simultaneously, graphene nanosheets were prepared. 5 grams of natural flake graphite powder were weighed and placed in a 500 ml beaker, along with 115 ml of concentrated sulfuric acid. The beaker was placed in an ice-water bath, and 15 grams of potassium permanganate powder was slowly added under vigorous stirring, strictly controlling the addition rate to ensure the reaction temperature did not exceed 20 degrees Celsius. The strong oxidizing properties of potassium permanganate would trigger a violent exothermic reaction; therefore, the reaction temperature had to be controlled using an ice bath and slow addition. After the potassium permanganate was added, the ice bath was removed, and the reaction system was heated to 38 degrees Celsius and maintained for 2 hours. During this process, potassium permanganate gradually inserted into the graphite interlayers and oxidized the graphite, causing the solution to gradually turn a dark brown, viscous consistency. Then, 230 ml of deionized water was slowly added to dilute the reaction system. The addition of water generated a large amount of heat, causing the solution temperature to rise rapidly. The temperature was then raised to 95 degrees Celsius and maintained for 30 minutes. During this stage, the oxidized graphite interlayers further expanded and exfoliated. Finally, 30 mL of 30% hydrogen peroxide solution was added to terminate the reaction. The solution color changed from dark brown to bright yellow, indicating that the permanganate ions were reduced to manganese ions. The reaction mixture was separated by centrifugation and repeatedly washed with deionized water until the pH of the supernatant was neutral, yielding a graphene oxide dispersion.

[0040] Weigh out a dispersion equivalent to 5 grams of graphene oxide and add 0.5 grams of hydrazine hydrate (mass ratio 1:10). Then, add an appropriate amount of ammonia to adjust the pH of the solution to 10. Reflux the mixture at 95°C for 24 hours. During the reduction process, hydrazine hydrate acts as a reducing agent, removing oxygen-containing functional groups from the surface of graphene oxide. The solution color gradually changes from yellow to black, indicating that the conjugated structure of graphene is restored. After reduction, obtain graphene precipitate by centrifugation and wash repeatedly with deionized water to remove residual hydrazine hydrate and ammonia. Freeze-dry the washed graphene dispersion. Freeze-drying effectively prevents the graphene sheets from recombinizing during the drying process, maintaining its high specific surface area. After freeze-drying for 48 hours, obtain black, loose graphene nanosheet powder.

[0041] The broadband absorption layer is now being prepared. 6 g of polyetheretherketone (PEEK) powder is weighed and added to 54 mL of concentrated sulfuric acid to prepare a 10% PEEK solution. The solution is stirred at room temperature for 4 hours to ensure complete dissolution. 1.8 g of functionalized multi-walled carbon nanotubes and 0.3 g of graphene nanosheets are weighed and added to 40 mL of N,N-dimethylformamide. The mixture is ultrasonically dispersed for 2 hours at a power of 500 W to obtain a stable dispersion. 1.8 g of surface-modified manganese-zinc ferrite nanoparticles are weighed and dispersed in 20 mL of N,N-dimethylformamide and ultrasonically treated for 30 minutes. In the above formulation, the mass fraction of manganese-zinc ferrite nanoparticles is 30%, the mass fraction of multi-walled carbon nanotubes is 5%, the mass fraction of graphene nanosheets is 2%, and the mass fraction of the PEEK matrix is ​​63%, with the sum of the mass fractions of all components equal to 100%. Carbon nanotube dispersions, graphene dispersions, and ferrite dispersions were mixed sequentially and slowly added to a polyetheretherketone (PEEK) solution under mechanical stirring at a rate of 7 mL / min to avoid localized precipitation of PEEK. After mixing, the mixture was transferred to a high-speed shear disperser and dispersed at 3000 rpm for 45 minutes to ensure uniform dispersion of each functional phase within the PEEK matrix. The uniformly dispersed mixture was then cast onto the surface of the impedance transition layer using a casting method, with the wet film thickness controlled by a casting knife to achieve a dry film thickness of 2.0 mm after curing. The sample was pre-dried in an 80°C oven for 1 hour to initially remove solvents, then transferred to a vacuum oven and dried at 120°C for 6 hours and then treated at 180°C for 4 hours to further remove solvents and initiate melting of the PEEK. Finally, the sample was placed in a hot press and hot-pressed at 280°C. The hot-pressing process employs a programmed pressurization method. First, the material is initially compacted at 5 MPa for 5 minutes, then the pressure is increased to 12 MPa and maintained for 30 minutes. Under high temperature and pressure, polyetheretherketone (PEEK) fully melts and impregnates all filler phases, while residual bubbles and solvents are expelled, forming a dense composite structure. After hot pressing, the temperature and pressure are slowly reduced, and the actual thickness of the broadband absorption layer is measured to be 2.0 mm.

[0042] Next, a composite metal reflective layer was applied. A 0.5 mm thick 5052 aluminum alloy sheet matching the sample size was selected. First, the aluminum sheet surface underwent chemical pretreatment. An alkaline degreasing solution was prepared, consisting of 50 g sodium hydroxide, 30 g sodium silicate, and 1 L deionized water. The aluminum sheet was immersed in the alkaline degreasing solution at 60°C for 15 minutes. The alkaline substances in the degreasing solution saponified the grease on the aluminum sheet surface and removed dirt. The aluminum sheet was then removed and thoroughly rinsed with deionized water. Next, the aluminum sheet was immersed in a 10% sulfuric acid solution and acid-washed at room temperature for 5 minutes. Acid washing removes the oxide film on the aluminum sheet surface and activates the surface, increasing surface roughness. It was then thoroughly rinsed again with deionized water. A chromic acid-phosphoric acid mixture was prepared, consisting of 200 g chromic acid, 100 g phosphoric acid, and 700 mL deionized water, with a chromic acid to phosphoric acid mass ratio of 2:1. The aluminum plate was immersed in a chromic acid-phosphoric acid mixture for chemical oxidation for 10 minutes, forming a dense conversion film and a micron-level rough structure on the surface. It was then thoroughly rinsed with deionized water and dried with compressed air. Two-component epoxy structural adhesive HN-7665 was mixed thoroughly with the curing agent at a ratio of 100:30 by mass, stirring until the adhesive was uniform and colorless. The structural adhesive was evenly applied to the pre-treated aluminum plate surface using a scraping method, controlling the coating thickness to 0.18 mm. Within 25 minutes of coating, the aluminum plate was bonded to the broadband absorption layer surface and rolled in a roller press at a pressure of 0.5 MPa and a speed of 1 meter per minute. The rolling process removes air bubbles from the adhesive layer and ensures uniform contact and full wetting between the aluminum plate and the broadband absorption layer. The sample was placed in an oven and pre-cured at 60°C for 4 hours, then cured at 120°C for 6 hours. After curing, the shear strength of the bonded interface was tested and found to be 19.5 MPa, which meets the design requirements.

[0043] Then, a carbon fiber reinforced protective layer was prepared. Four layers of plain-weave carbon fiber fabric were cut, each layer matching the sample size. The carbon fiber fabric was sequentially laid on the surface of the metal reflective layer, with the fiber directions alternating at 0°, 90°, 0°, and 90° to achieve good isotropy. An epoxy resin system was prepared, including 100g of epoxy resin E-51, 12g of low-viscosity reactive diluent, 30g of polyamide curing agent, and 0.5g of defoamer. All components were thoroughly mixed and stirred evenly. The composite sample and resin system were placed together in a vacuum-assisted resin transfer molding device. A resin inlet was set at one end of the sample, and a vacuum outlet at the other end. The vacuum pump was started, and the vacuum level was reduced to -0.092 MPa. The resin inlet valve was opened, and under vacuum, the resin system was drawn in from the inlet and gradually impregnated the carbon fiber fabric. The resin was observed to flow rapidly along the fiber direction and propel towards the vacuum outlet. When the resin reached the vacuum outlet, the resin inlet valve and the vacuum outlet valve were closed to maintain the system under vacuum. The resin was initially gelled at 60°C for 2 hours, then cured at 120°C for 4 hours, and finally cured at 150°C for 2 hours. After curing, the sample was removed, and the actual thickness of the carbon fiber reinforced protective layer was measured to be 1.2 mm. The sample was cut and observed under a microscope, showing that the carbon fibers were fully impregnated with resin, and the porosity was less than 2%.

[0044] Finally, the overall composite material underwent post-processing. The prepared five-layer composite material was edge-trimmed on a CNC milling machine to remove burrs and irregularities, ensuring a dimensional accuracy of ±0.1 mm. The sample was then placed in an oven at 150°C for 4 hours for stress relaxation treatment. This process eliminates internal stress caused by differences in the thermal expansion coefficients of the layers and curing shrinkage during preparation. After stress relaxation, a polyurethane protective coating was sprayed onto the surface of the composite material using a spraying device, with the coating thickness controlled at 65 micrometers. After the polyurethane coating cured for 24 hours, the finished composite material of Example 1 was obtained. The total thickness of the overall composite material was measured to be 5.45 mm, and the areal density was 4.2 kg / m².

[0045] Example 2 The composite material prepared in this embodiment differs from that in Example 1 in terms of composition and preparation parameters.

[0046] The preparation of the surface-modified carbonyl iron powder was the same as in Example 1. In the preparation of the high permeability absorbing layer, 130 grams of surface-modified carbonyl iron powder and 70 grams of epoxy resin E-51 were weighed, with the carbonyl iron powder having a mass fraction of 65%. Other preparation steps were the same as in Example 1, resulting in a high permeability absorbing layer substrate with a thickness of 1.0 mm.

[0047] In the preparation of the impedance transition layer, the ratio of silicon carbide whiskers to flake carbonyl iron powder was adjusted. 1.5 g of silicon carbide whiskers and 3 g of flake carbonyl iron powder were weighed and added to a solution containing 5 g of solid polyimide. The mass fraction of the silicon carbide whiskers was 15%, and the mass fraction of the flake carbonyl iron powder was 30%. Other preparation steps were the same as in Example 1, resulting in an impedance transition layer with a thickness of 0.65 mm.

[0048] In the preparation of the broadband absorption layer, the proportions of each functional phase were adjusted. 6 grams of polyetheretherketone powder, 1.5 grams of manganese-zinc ferrite nanoparticles, 0.48 grams of multi-walled carbon nanotubes, and 0.12 grams of graphene nanosheets were weighed. In this ratio, the mass fraction of manganese-zinc ferrite nanoparticles was 25%, the mass fraction of multi-walled carbon nanotubes was 8%, the mass fraction of graphene nanosheets was 2%, and the mass fraction of the polyetheretherketone matrix was 65%, with the sum of the mass fractions of all components equal to 100%. Other preparation steps were the same as in Example 1, resulting in a broadband absorption layer with a thickness of 2.0 mm.

[0049] The preparation of the metal reflective layer and the carbon fiber reinforced protective layer was the same as in Example 1. The final composite material product of Example 2 was obtained, with a total thickness of 5.45 mm and an areal density of 4.1 kg / m².

[0050] Example 3 The composite material prepared in this embodiment also had some adjustments in its preparation process.

[0051] In the preparation of surface-modified carbonyl iron powder, the drying temperature was selected as 90 degrees Celsius, the amount of silane coupling agent was 4% of the mass of carbonyl iron powder, the reaction temperature was 65 degrees Celsius, and the reaction time was 5 hours.

[0052] In the preparation of the high magnetic permeability absorbing layer, the mass fraction of carbonyl iron powder was set to 70%. During the preparation process, the high shear dispersion rotation speed was set to 2250 rpm, the vacuum degree of vacuum degassing was -0.085 MPa, and the amount of curing agent was 32.5% of the epoxy resin mass, all of which are mid-range values ​​within the parameter range. A high magnetic permeability absorbing layer substrate with a thickness of 1.0 mm was obtained.

[0053] In the preparation of the impedance transition layer, the mass fraction of silicon carbide whiskers was set to 20%, the mass fraction of flake carbonyl iron powder was set to 35%, and the mass fraction of polyimide matrix was set to 45%, with the sum of the mass fractions of all components equal to 100%. The solid content of the polyimide solution was set to 17.5%. The ultrasonic dispersion and mechanical stirring times were each 30 minutes. The wet film thickness was controlled to be 3.5 mm. The heating rate during the heat treatment process was controlled to be 2.5 degrees Celsius per minute. An impedance transition layer with a thickness of 0.65 mm was obtained.

[0054] In the preparation of the broadband absorption layer, the proportions of each component were adjusted to cover intermediate values. 6 g of polyetheretherketone (PEEK) powder, 1.8 g of manganese-zinc ferrite nanoparticles, 0.33 g of multi-walled carbon nanotubes, and 0.15 g of graphene nanosheets were weighed. In this formulation, the mass fraction of manganese-zinc ferrite nanoparticles was 30%, the mass fraction of multi-walled carbon nanotubes was 5.5%, the mass fraction of graphene nanosheets was 2.5%, and the mass fraction of the PEEK matrix was 62%, with the sum of the mass fractions of all components equal to 100%. The mass fraction of the PEEK solution was set to 10%. The rate at which the mixture was added to the PEEK solution was controlled at 7.5 mL per minute. During hot pressing, a programmed pressure was used, first maintaining a pressure of 5 MPa for 5 minutes, then increasing to 12.5 MPa and maintaining it for 30 minutes. A broadband absorption layer with a thickness of 2.0 mm was obtained.

[0055] In the preparation of the metal reflective layer, the coating thickness of the epoxy structural adhesive was controlled at 0.175 mm. Lamination and rolling operations were completed within 27.5 minutes after adhesive application.

[0056] In the preparation of the carbon fiber reinforced protective layer, the amount of reactive diluent used in the epoxy resin system was 12.5 parts. The vacuum degree in the vacuum-assisted resin transfer molding process was set to -0.0925 MPa.

[0057] The final composite material product of Example 3 was obtained, with a total thickness of 5.45 mm and a surface density of 4.15 kg per square meter.

[0058] Example 4 In the preparation of the surface-modified carbonyl iron powder of the composite material prepared in this embodiment, the drying temperature was selected as 100 degrees Celsius, the amount of silane coupling agent was 5% of the mass of carbonyl iron powder, the reaction temperature was 70 degrees Celsius, and the reaction time was 6 hours.

[0059] In the preparation of the high magnetic permeability absorbing layer, the mass fraction of carbonyl iron powder was set to 75%. 150 grams of surface-modified carbonyl iron powder and 50 grams of epoxy resin E-51 were weighed. The high-shear dispersion rotation speed was set to 2500 rpm, the vacuum degree for vacuum degassing was -0.09 MPa, and the amount of curing agent was 35% of the epoxy resin mass, all at the upper limit of the parameter range. The layer thickness was controlled to 1.0 mm, consistent with Examples 1-3 for comparison.

[0060] In the preparation of the impedance transition layer, the mass fraction of silicon carbide whiskers was set to 25%, the mass fraction of flake carbonyl iron powder was set to 40%, and the mass fraction of polyimide matrix was set to 35%, with the sum of the mass fractions of all components equal to 100%. 2.5 g of silicon carbide whiskers and 4 g of flake carbonyl iron powder were weighed and added to a solution containing 3.5 g of solid polyimide. The solid content of the polyimide solution was set to 20%. The wet film thickness was controlled to 4 mm. The heating rate during the heat treatment process was controlled to 3 degrees Celsius per minute. An impedance transition layer with a thickness of 0.65 mm was obtained.

[0061] In the preparation of the broadband absorption layer, the proportions of each component were adjusted to reflect the upper limit. 6 g of polyetheretherketone (PEEK) powder, 2.1 g of manganese-zinc ferrite nanoparticles, 0.18 g of multi-walled carbon nanotubes, and 0.18 g of graphene nanosheets were weighed. In this ratio, the mass fraction of manganese-zinc ferrite nanoparticles was 35%, the mass fraction of multi-walled carbon nanotubes was 3%, the mass fraction of graphene nanosheets was 3%, and the mass fraction of the PEEK matrix was 59%, with the sum of the mass fractions of each component equal to 100%. The mass fraction of the PEEK solution was set to 12%. The rate at which the mixture was added to the PEEK solution was controlled at 10 mL per minute. During hot pressing, a programmed pressure was used, first maintaining a pressure of 5 MPa for 5 minutes, then increasing to 15 MPa and maintaining it for 30 minutes. A broadband absorption layer with a thickness of 2.0 mm was obtained.

[0062] In the preparation of the metal reflective layer, the coating thickness of the epoxy structural adhesive was controlled to be 0.20 mm. The bonding and rolling operations were completed 30 minutes after adhesive application, which is within the upper limit of the time requirement.

[0063] In the preparation of the carbon fiber reinforced protective layer, the amount of reactive diluent used in the epoxy resin system is 15 parts. The vacuum degree in the vacuum-assisted resin transfer molding process is set to -0.095 MPa.

[0064] The final composite material product of Example 4 was obtained, with a total thickness of 5.45 mm and a surface density of 4.3 kg per square meter.

[0065] Example 5 In the composite material prepared in this embodiment, the preparation of the surface-modified carbonyl iron powder is the same as in Example 1.

[0066] In the preparation of the high permeability absorbing layer, the mass fraction of carbonyl iron powder was maintained at 70%. The layer thickness was adjusted to 0.8 mm. Other parameters were the same as in Example 1.

[0067] In the preparation of the impedance transition layer, the mass fraction of silicon carbide whiskers was 20%, the mass fraction of flake carbonyl iron powder was 35%, and the mass fraction of polyimide matrix was 45%. The wet film thickness was adjusted to achieve a cured thickness of 0.5 mm. Other parameters were the same as in Example 3.

[0068] In the preparation of the broadband absorption layer, the proportions of each component were the same as in Example 3, namely 30% manganese-zinc ferrite nanoparticles, 5.5% multi-walled carbon nanotubes, 2.5% graphene nanosheets, and 62% polyetheretherketone matrix. The layup thickness was adjusted to 1.5 mm. Other parameters were the same as in Example 3.

[0069] The metal reflective layer was made of a 0.3 mm thick aluminum alloy sheet. Other preparation steps were the same as in Example 3.

[0070] In the preparation of the carbon fiber reinforced protective layer, three layers of plain-weave carbon fiber fabric were laid to achieve a cured thickness of 0.8 mm. The volume fraction of carbon fiber was controlled at 55%. Other parameters were the same as in Example 3.

[0071] The final composite material product of Example 5 was obtained, with a total thickness of 3.9 mm, which is close to the lower limit of the overall thickness range of 4.0 to 6.5 mm, and a surface density of 3.6 kg per square meter.

[0072] Example 6 The preparation of the surface-modified carbonyl iron powder of the composite material prepared in this embodiment is the same as that in Example 4.

[0073] In the preparation of the high permeability absorbing layer, the mass fraction of carbonyl iron powder was maintained at 70%. The layer thickness was adjusted to 1.2 mm. Other parameters were the same as in Example 1.

[0074] In the preparation of the impedance transition layer, the mass fraction of silicon carbide whiskers was 20%, the mass fraction of flake carbonyl iron powder was 35%, and the mass fraction of polyimide matrix was 45%. The wet film thickness was adjusted to achieve a cured thickness of 0.8 mm. Other parameters were the same as in Example 3.

[0075] In the preparation of the broadband absorption layer, the proportions of each component were the same as in Example 3. The thickness was adjusted to 2.5 mm. Other parameters were the same as in Example 3.

[0076] The metal reflective layer was made of a 0.6 mm thick aluminum alloy sheet. Other preparation steps were the same as in Example 3.

[0077] In the preparation of the carbon fiber reinforced protective layer, four layers of plain-weave carbon fiber fabric were laid to achieve a cured thickness of 1.5 mm. The volume fraction of carbon fiber was controlled at 65%. Other parameters were the same as in Example 3.

[0078] The final composite material product of Example 6 was obtained, with a total thickness of 6.6 mm, which is close to the upper limit of the overall thickness range of 4.0 to 6.5 mm, and a surface density of 5.1 kg per square meter.

[0079] Comparative Example 1 This comparative example is used to verify the importance of carbonyl iron powder in the high permeability absorption layer. In this comparative example, the carbonyl iron powder in the high permeability absorption layer was removed, and only pure epoxy resin was used as the first layer.

[0080] Prepare a pure epoxy resin layer. Weigh 60 grams of epoxy resin E-51 and 19.5 grams of polyamide curing agent, mix thoroughly, and then perform vacuum degassing. Pour the mixture into a mold and control the thickness to 1.0 mm. Curing is performed according to the same procedure as in Example 1 to obtain a pure epoxy resin layer.

[0081] The preparation of the impedance transition layer, broadband absorption layer, metal reflective layer and carbon fiber reinforced protective layer is the same as in Example 1.

[0082] The final composite material product of Comparative Example 1 was obtained, with a total thickness of 5.45 mm and a surface density of 3.5 kg / m². Due to the removal of high-density carbonyl iron powder, the surface density of Comparative Example 1 was significantly lower than that of Example 1.

[0083] Comparative Example 2 This comparative example is used to verify the importance of the impedance transition layer. In this example, the impedance transition layer is removed, and a high-permeability absorbing layer is directly composited with a broadband absorbing layer.

[0084] The high permeability absorbing layer was prepared in the same manner as in Example 1. The broadband absorbing layer was directly deposited on the surface of the high permeability absorbing layer, and its preparation method was the same as in Example 1. The preparation of the metal reflective layer and the carbon fiber reinforced protective layer was also the same as in Example 1.

[0085] The final composite material product of Comparative Example 2 was obtained, with a total thickness of 4.8 mm and a surface density of 4.0 kg per square meter.

[0086] Comparative Example 3 This comparative example is used to verify the importance of the synergistic effect of multiple functional phases in a broadband absorber layer. In this comparative example, the broadband absorber layer uses only manganese-zinc ferrite nanoparticles as the functional phase, omitting multi-walled carbon nanotubes and graphene nanosheets.

[0087] The preparation of the high permeability absorption layer and the impedance transition layer is the same as in Example 1.

[0088] In the preparation of the broadband absorption layer, 6 grams of polyetheretherketone powder and 1.8 grams of surface-modified manganese-zinc ferrite nanoparticles were weighed. In this ratio, the mass fraction of manganese-zinc ferrite nanoparticles was 30%, the mass fraction of polyetheretherketone matrix was 70%, and the sum of the mass fractions was 100%. Other preparation steps were the same as in Example 1, resulting in a broadband absorption layer with a thickness of 2.0 mm.

[0089] The preparation of the metal reflective layer and the carbon fiber reinforced protective layer is the same as in Example 1.

[0090] The final composite material product of Comparative Example 3 was obtained, with a total thickness of 5.45 mm and a surface density of 4.0 kg per square meter.

[0091] Comparative Example 4 This comparative example is used to verify the importance of the metallic reflective layer. In this comparative example, the metallic reflective layer is removed, and the broadband absorbing layer is directly composited with the carbon fiber reinforced protective layer.

[0092] The preparation of the high permeability absorbing layer, impedance transition layer, and broadband absorbing layer is the same as in Example 1. The carbon fiber reinforced protective layer is directly laid on the surface of the broadband absorbing layer, and the preparation method is the same as in Example 1.

[0093] The final composite material product of Comparative Example 4 was obtained, with a total thickness of 4.95 mm and a surface density of 3.8 kg / m².

[0094] The composite materials prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were subjected to systematic performance tests to comprehensively evaluate the technical effects of the present invention.

[0095] Electromagnetic shielding effectiveness testing: The electromagnetic shielding effectiveness of the composite material in the 0.1 to 18 GHz frequency band was tested using an Agilent N5230C vector network analyzer and the coaxial transmission line method. Before testing, the composite material samples were processed into ring-shaped standard samples with an outer diameter of 7.0 mm and an inner diameter of 3.04 mm, maintaining the actual thickness of each embodiment and comparative example. The samples were placed in a coaxial fixture, which was connected to the vector network analyzer via a coaxial cable. The system was calibrated before testing using a three-point calibration with a standard short-circuit plate, an open-circuit plate, and a matched load to ensure testing accuracy. During testing, the vector network analyzer emitted electromagnetic wave signals, which were transmitted to the sample via the coaxial line. The transmitted and reflected electromagnetic wave signals were measured, and the reflection loss, absorption loss, and shielding effectiveness of the material were calculated based on the scattering parameters S11 and S21. Each sample was tested three times, and the average value was taken as the final result.

[0096] Tensile strength testing was conducted according to the national standard GB / T 1040.1-2018. Composite material samples were processed into standard tensile specimens with dimensions of 150 mm in length, 10 mm in width, and the actual thickness of the sample. Tensile testing was performed using a universal testing machine at a tensile rate of 2 mm per minute. The maximum load at fracture was recorded, and the tensile strength was calculated. Five specimens were tested for each group of samples, and the average value was taken.

[0097] Bending strength testing was conducted according to the national standard GB / T 1449-2005. Composite material samples were processed into rectangular specimens with dimensions of 80 mm in length and 10 mm in width. A universal testing machine was used for three-point bending tests, with a support span set at 60 mm and a loading rate of 2 mm per minute. The maximum load at fracture was recorded, and the bending strength was calculated. Five specimens were tested in each group, and the average value was taken.

[0098] Interlaminar shear strength testing was conducted according to the national standard GB / T 3357-2018. Composite material samples were fabricated into short beam shear specimens with dimensions of 20 mm in length and 6 mm in width. A universal testing machine was used for the short beam shear test, with a support span set at 10 mm and a loading rate of 1 mm per minute. The maximum load at shear failure was recorded, and the interlaminar shear strength was calculated. Five specimens were tested for each group of samples, and the average value was taken.

[0099] Impact strength testing was conducted according to the national standard GB / T 1043.1-2008. Composite material samples were processed into unnotched impact test specimens with dimensions of 80 mm in length and 10 mm in width. Impact testing was performed using a pendulum impact testing machine, and the energy absorbed upon sample failure was recorded to calculate the impact strength. Five specimens were tested for each group of samples, and the average value was taken.

[0100] The damp heat aging test was conducted according to the national standard GB / T 2423.3-2016. The composite material samples were placed in a constant temperature and humidity chamber, with the temperature set at 85 degrees Celsius and the relative humidity at 85%. After 1000 hours of continuous testing, the samples were removed and placed under standard atmospheric conditions for 24 hours. Then, their electromagnetic shielding effectiveness and mass change were tested, and the performance retention rate and mass increase rate were calculated.

[0101] Salt spray corrosion testing was conducted according to the national standard GB / T 10125-2012. A 5% sodium chloride solution was prepared as the salt spray corrosion medium. The composite material samples were placed in a salt spray test chamber, the temperature was set to 35 degrees Celsius, and continuous spraying was used. After 500 hours of continuous testing, the samples were removed, rinsed with deionized water, and dried. The surface corrosion was observed, and the change in electromagnetic shielding effectiveness was tested.

[0102] Table 1 summarizes the electromagnetic shielding effectiveness test results of Examples 1 to 6 and Comparative Examples 1 to 4. The shielding effectiveness data include the average shielding effectiveness in the low-frequency band of 0.1 to 2 GHz, the mid-frequency band of 2 to 8 GHz, and the high-frequency band of 8 to 18 GHz, as well as the average shielding effectiveness across the entire 0.1 to 18 GHz frequency band.

[0103] Table 1 Electromagnetic shielding effectiveness test results sample Low-frequency shielding effectiveness (dB) Mid-band shielding effectiveness (dB) High-frequency shielding effectiveness (dB) Average shielding effectiveness across the entire frequency band (dB) Effective absorption bandwidth (GHz) Example 1 38.5 47.2 42.8 42.8 7.8 Example 2 35.2 44.5 40.1 39.9 7.2 Example 3 37.8 46.5 42.3 42.2 7.6 Example 4 40.2 48.8 44.5 44.5 8.3 Example 5 34.8 43.2 39.5 39.2 6.9 Example 6 39.5 47.8 43.2 43.5 8 Comparative Example 1 22.3 42.8 38.5 34.5 5.8 Comparative Example 2 30.5 38.2 35.8 34.8 4.5 Comparative Example 3 35.8 43.5 32.5 37.3 5.2 Comparative Example 4 33.2 40.8 37.2 37.1 6.2 As shown in Table 1, the composite materials prepared in Examples 1 to 6 exhibit excellent electromagnetic shielding performance across the entire frequency band from 0.1 to 18 GHz, with an average shielding effectiveness ranging from 39.2 to 44.5 dB and an effective absorption bandwidth between 6.9 and 8.3 GHz. Example 4 showed the highest shielding effectiveness because it used the upper limit of the carbonyl iron powder mass fraction (75%), enhancing the magnetic loss capability in the low-frequency band, while the manganese-zinc ferrite nanoparticle mass fraction reached 35%, improving the absorption performance in the mid-to-high frequency band. Example 5 showed relatively low shielding effectiveness because the thickness of each layer in this example was the lower limit, with a total thickness of only 3.9 mm. This resulted in a shorter propagation path for electromagnetic waves in the material and a relatively smaller attenuation.

[0104] Comparative Example 1 exhibits significantly lower shielding effectiveness in the low-frequency band compared to all other examples, at only 22.3 dB. This underscores the importance of carbonyl iron powder in the high-permeability absorption layer for absorbing low-frequency electromagnetic waves. The natural ferromagnetic resonance frequency of carbonyl iron powder lies precisely in the 0.1 to 2 GHz low-frequency range, and its absence results in a lack of effective magnetic loss mechanisms in this frequency band. Comparative Example 2 demonstrates significantly lower shielding effectiveness across all frequency bands compared to Example 1, particularly with an effective absorption bandwidth of only 4.5 GHz. This indicates that the impedance transition layer plays a crucial role in achieving gradient impedance matching and reducing interface reflection loss. Comparative Example 3 exhibits a shielding effectiveness of only 32.5 dB in the high-frequency band, significantly lower than the 42.8 dB of Example 1. This suggests that the conductive network formed by multi-walled carbon nanotubes and graphene nanosheets contributes significantly to dielectric loss in the high-frequency band. The average shielding effectiveness across the entire frequency band of Comparative Example 4 is 37.1 dB, which is lower than 42.8 dB of Example 1. This indicates that the metal reflective layer plays an important role in improving the overall shielding effectiveness by reflecting residual transmitted electromagnetic waves to form a secondary absorption effect.

[0105] Table 2 summarizes the mechanical performance test results of Examples 1 to 6 and Comparative Examples 1 to 4.

[0106] Table 2 Mechanical Performance Test Results sample Tensile strength (MPa) Bending strength (MPa) Interlaminar shear strength (MPa) <![CDATA[Impact strength (kJ / m 2) > <![CDATA[Areal density (kg / m 2) > Example 1 208 315 40.5 52.3 4.2 Example 2 195 295 37.2 48.5 4.1 Example 3 205 310 39.8 51.5 4.15 Example 4 220 335 43.2 56.8 4.3 Example 5 185 280 35.5 45.2 3.6 Example 6 228 348 44.5 58.5 5.1 Comparative Example 1 175 265 32.8 42.5 3.5 Comparative Example 2 198 305 28.5 50.8 4 Comparative Example 3 202 308 38.5 50.5 4 Comparative Example 4 188 285 38.2 48.2 3.8 As shown in Table 2, the composite materials prepared in Examples 1 to 6 all exhibit excellent mechanical properties, with tensile strength ranging from 185 to 228 MPa, flexural strength from 280 to 348 MPa, interlaminar shear strength from 35.5 to 44.5 MPa, impact strength from 45.2 to 58.5 kJ / m², and areal density from 3.6 to 5.1 kg / m². These mechanical properties fully meet the load-bearing requirements of the UAV shell structure. Example 6, due to the use of the upper limit for each layer thickness, achieves a total thickness of 6.6 mm, thus exhibiting the highest mechanical strength, but also a correspondingly increased areal density. Example 5, using the lower limit for each layer thickness, has the lowest areal density, but also relatively lower mechanical strength, reflecting the trade-off between thickness and performance.

[0107] Comparative Example 1, due to the removal of high-density carbonyl iron powder, had the lowest areal density, but also the worst mechanical properties. This is because the carbonyl iron powder not only provides magnetic loss function, but its uniform dispersion in the resin matrix also acts as a reinforcing phase, improving the overall strength of the material. Comparative Example 2 had an interlaminar shear strength of only 28.5 MPa, significantly lower than the 40.5 MPa of Example 1. This indicates that the impedance transition layer not only has electromagnetic functions, but the high strength and high modulus of its polyimide matrix also contribute to the overall mechanical properties of the composite material. Furthermore, the presence of this layer creates a stronger interfacial bond between adjacent layers. Comparative Example 4, due to the removal of the metal reflective layer, showed a decrease in both stiffness and strength, indicating that the metal layer also enhances the mechanical properties of the composite material.

[0108] Table 3 summarizes the environmental stability test results of Examples 1, 3, and Comparative Examples 1 to 4.

[0109] Table 3 Environmental stability test results sample Shielding effectiveness retention rate after damp heat aging (%) Weight gain rate after damp heat aging (%) Shielding effectiveness retention rate after salt spray corrosion (%) Surface condition after salt spray corrosion Example 1 93.5 1.2 96.2 No obvious corrosion Example 3 94.2 1.1 96.8 No obvious corrosion Comparative Example 1 88.5 1.8 92.5 Slight corrosion Comparative Example 2 90.2 1.5 93.8 Slight corrosion Comparative Example 3 92.8 1.3 95.5 No obvious corrosion Comparative Example 4 89.5 1.4 88.2 Obvious corrosion As shown in Table 3, the composite materials prepared in Examples 1 and 3 exhibit excellent environmental stability. After 1000 hours of damp heat aging, the shielding effectiveness retention rate is between 93.5% and 94.2%, with a mass increase rate of only 1.1% to 1.2%, indicating that the material has good resistance to damp heat. After 500 hours of salt spray corrosion, the shielding effectiveness retention rate is between 96.2% and 96.8%, with no obvious surface corrosion, indicating that the material has excellent corrosion resistance. This is mainly attributed to the excellent weather resistance of high-performance matrix materials such as polyetheretherketone and polyimide, as well as the effective blocking of corrosive media penetration by the surface polyurethane protective coating.

[0110] The environmental stability of Comparative Examples 1 to 3 was slightly lower than that of the Example, but still remained within an acceptable range. In Comparative Example 4, due to the removal of the metal reflective layer, the internal absorbing phase was directly exposed to the pores of the carbon fiber reinforced protective layer. Under salt spray corrosion, the corrosive medium could more easily penetrate the interior, leading to oxidation and corrosion of components such as manganese-zinc ferrite. The shielding effectiveness retention rate after salt spray corrosion was only 88.2%, and obvious corrosion spots appeared on the surface. This indicates that the metal reflective layer not only has electromagnetic reflection capabilities but also protects the internal functional layers from environmental corrosion.

[0111] Based on the comprehensive analysis of the above test results, the composite material prepared in Example 4 exhibits the best overall performance in terms of electromagnetic shielding effectiveness, mechanical properties, and environmental stability, and can be considered as the preferred embodiment of the present invention. This embodiment uses a composition ratio of 75% carbonyl iron powder, 35% manganese-zinc ferrite nanoparticles, 3% multi-walled carbon nanotubes, and 3% graphene nanosheets. It achieves an average shielding effectiveness of 44.5 dB across the entire frequency band from 0.1 to 18 GHz, an effective absorption bandwidth of 8.3 GHz, a tensile strength of 220 MPa, a flexural strength of 335 MPa, an interlaminar shear strength of 43.2 MPa, an impact strength of 56.8 kJ / m², and an areal density of 4.3 kg / m², resulting in a weight reduction of approximately 50% compared to traditional metal shielding materials.

[0112] The reason why the composite material of this invention can achieve excellent electromagnetic shielding performance is that the multi-layer gradient impedance matching structure design and the synergistic effect of multiple functions generate a multi-electromagnetic wave attenuation mechanism.

[0113] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principle of the present invention should be included within the scope of protection of the present invention.

Claims

1. A composite material that facilitates shielding of a drone's own engine from electromagnetic interference, characterized in that, The composite material is composed of five layers sequentially from the outside to the inside, specifically including: A high magnetic permeability absorbing layer, with a thickness of 0.8 to 1.2 mm, is composed of an epoxy resin matrix and surface-modified carbonyl iron powder, wherein the surface-modified carbonyl iron powder has a mass fraction of 65% to 75% and a particle size range of 3 to 8 micrometers. An impedance transition layer, with a thickness of 0.5 to 0.8 mm, is located inside the high permeability absorption layer. It is composed of a polyimide matrix, silicon carbide whiskers, and flake carbonyl iron powder. The silicon carbide whiskers have a mass fraction of 15% to 25% and an aspect ratio of 20 to 50. The flake carbonyl iron powder has a mass fraction of 30% to 40% and a flake diameter of 5 to 15 micrometers and a thickness of 0.5 to 1.5 micrometers. A broadband absorption layer, with a thickness of 1.5 to 2.5 mm, is located inside the impedance transition layer. It is composed of a polyetheretherketone matrix, manganese zinc ferrite nanoparticles, multi-walled carbon nanotubes, and graphene nanosheets. The manganese zinc ferrite nanoparticles have a mass fraction of 25% to 35% and an average particle size of 30 to 80 nm. The multi-walled carbon nanotubes have a mass fraction of 3% to 8% and an outer diameter of 10 to 30 nm and a length of 5 to 20 μm. The graphene nanosheets have a mass fraction of 1% to 3% and a sheet diameter of 1 to 5 μm and a thickness of 3 to 10 nm. A metal reflective layer, with a thickness of 0.3 to 0.6 mm, is located inside the broadband absorption layer. It is made of aluminum alloy sheet or copper alloy sheet, and the surface roughness is controlled to be 0.4 to 0.8 micrometers. A carbon fiber reinforced protective layer, with a thickness of 0.8 to 1.5 mm, is located inside the metal reflective layer and is composed of carbon fiber woven fabric and epoxy resin, wherein the volume fraction of the carbon fiber is 55% to 65%.

2. The composite material according to claim 1, characterized in that, The surface-modified carbonyl iron powder is obtained by surface modification treatment with a silane coupling agent. Specifically, the carbonyl iron powder is vacuum dried at 80 to 100 degrees Celsius for 2 hours, then dispersed in anhydrous ethanol, and γ-aminopropyltriethoxysilane coupling agent with a mass fraction of 3% to 5% of the carbonyl iron powder is added. The mixture is mechanically stirred at 60 to 70 degrees Celsius for 4 to 6 hours to allow the silane molecules to undergo hydrolysis and condensation reactions on the surface of the iron powder to form a coating layer. After the reaction is completed, the powder is centrifuged, washed three times with anhydrous ethanol, and vacuum dried at 80 degrees Celsius for 4 hours to obtain the final product.

3. The composite material according to claim 1, characterized in that, The manganese-zinc ferrite nanoparticles were prepared by a sol-gel method. Specifically, manganese nitrate, zinc nitrate, and ferric nitrate were dissolved in deionized water in stoichiometric proportions to prepare a mixed solution with a total metal ion concentration of 0.5 to 0.8 mol / L, wherein the molar ratio of manganese, zinc, and iron was 0.4 to 0.6:0.2 to 0.4:1.8 to 2.

2. Sodium hydroxide solution was added dropwise to the mixed solution under vigorous stirring to adjust the pH value to 10.5 to 11.

5. A precursor gel is generated by co-precipitating metal ions. The gel is aged at 80 to 90 degrees Celsius for 12 to 18 hours, then repeatedly washed with deionized water until neutral, and dried at 100 degrees Celsius for 8 hours to obtain precursor powder. The precursor powder is heated to 800 to 900 degrees Celsius in a muffle furnace at a heating rate of 5 degrees Celsius per minute and held at that temperature for 2 to 4 hours for high-temperature sintering. The powder is then cooled to room temperature with the furnace to obtain spinel-structured manganese-zinc ferrite nanoparticles.

4. The composite material according to claim 1, characterized in that, The multi-walled carbon nanotubes underwent a dual functionalization modification treatment involving acidification and grafting. Specifically, the multi-walled carbon nanotubes were refluxed in a mixed acid of concentrated sulfuric acid and concentrated nitric acid at 80°C for 6 to 8 hours, with a volume ratio of concentrated sulfuric acid to concentrated nitric acid of 3:

1. The treated carbon nanotubes were repeatedly washed with deionized water until neutral and then vacuum-dried overnight at 80°C. The acidified carbon nanotubes were then dispersed in N,N-dimethylformamide, and excess thionyl chloride was added. The mixture was refluxed at 70 to 80°C for 12 hours to convert the surface carboxyl groups into acyl chloride groups. After filtering to remove excess thionyl chloride, the product was redispersed in N,N-dimethylformamide, and aminopropyltriethoxysilane was added. The mixture was reacted at 60°C for 24 hours to graft silane molecules onto the carbon nanotube surface via amide bonds. The final product was subjected to Soxhlet extraction to remove unreacted reagents and vacuum-dried at 80°C for 12 hours to obtain functionalized multi-walled carbon nanotubes.

5. The composite material according to claim 1, characterized in that, The graphene nanosheets were obtained by chemical reduction of graphene oxide prepared by a modified Hummers method. Specifically, natural flake graphite powder was mixed with concentrated sulfuric acid, and potassium permanganate was slowly added under ice bath conditions while controlling the reaction temperature to not exceed 20 degrees Celsius. The temperature was then raised to 35 to 40 degrees Celsius and reacted for 2 hours. Deionized water was added for dilution, and the temperature was raised to 95 degrees Celsius and reacted for 30 minutes. Finally, hydrogen peroxide was added to terminate the reaction. The reaction product was centrifuged and repeatedly washed with deionized water until neutral to obtain a graphene oxide dispersion. The graphene oxide dispersion was mixed with hydrazine hydrate at a mass ratio of 1:

10. Ammonia was added to adjust the pH to 10, and the mixture was refluxed at 95 degrees Celsius for 24 hours. The reduction product was centrifuged, washed with deionized water, and freeze-dried to obtain graphene nanosheets.

6. The method for preparing the composite material according to any one of claims 1 to 5, characterized in that, Includes the following steps: Step 1: Prepare a high magnetic permeability absorption layer. Surface-modified carbonyl iron powder is added to epoxy resin at a mass fraction of 70%. The epoxy resin is type E-51 with an epoxy value of 0.48 to 0.54 mol / 100g. The mixture is dispersed for 30 minutes using a high-shear disperser at a speed of 2000 to 2500 rpm. Then, a polyamide curing agent at a mass fraction of 30% to 35% of the epoxy resin is added and stirring is continued for 10 minutes. The mixture is then vacuum degassed for 20 minutes under a vacuum degree of -0.08 to -0.09 MPa. The degassed mixture is poured into a stainless steel mold pre-coated with a release agent, with a thickness controlled to 1.0 mm. Pre-curing is performed at 60°C for 2 hours, curing at 120°C for 4 hours, and post-curing at 150°C for 2 hours. The mixture is then cooled to room temperature in the oven and demolded to obtain the high magnetic permeability absorption layer substrate. Step 2: Prepare the impedance transition layer. Dissolve polyimide powder in N-methylpyrrolidone solvent to prepare a polyimide solution with a solid content of 15% to 20%. Add silicon carbide whiskers and flake carbonyl iron powder to the polyimide solution according to the designed mass fraction. Disperse the mixture for 1 hour using a combination of ultrasonic dispersion and mechanical stirring. The ultrasonic dispersion has an ultrasonic power of 500 watts and an ultrasonic frequency of 20 kHz. Coat the uniformly dispersed mixture onto the surface of the high permeability absorption layer substrate obtained in Step 1 using a scraping method, and control the wet film thickness to be 3 to 4 mm. Pre-bake at 80 degrees Celsius for 2 hours, and then process it in a vacuum oven according to the programmed temperature rise: 120 degrees Celsius for 2 hours, 180 degrees Celsius for 2 hours, 250 degrees Celsius for 1 hour, and imidize at 320 degrees Celsius for 4 hours. Step 3: Prepare a broadband absorption layer. Dissolve polyetheretherketone (PEEK) powder in concentrated sulfuric acid to prepare a PEEK solution with a mass fraction of 8% to 12%. The average molecular weight of the PEEK powder is 25,000 to 30,000. Functionalized multi-walled carbon nanotubes and graphene nanosheets are pre-dispersed in N,N-dimethylformamide and ultrasonically treated for 2 hours to obtain a stable dispersion. Manganese-zinc ferrite nanoparticles are surface-treated with γ-glycidyl etheroxypropyltrimethoxysilane coupling agent and then dispersed in N,N-dimethylformamide. The three dispersions are then combined according to... After the designed proportions are mixed, the mixture is slowly added to the polyetheretherketone solution under mechanical stirring. After mixing, the mixture is dispersed in a high-speed shear disperser at 3000 rpm for 45 minutes. The uniformly dispersed mixture is then laid on the surface of the impedance transition layer obtained in step two by casting, with the thickness controlled to be 2.0 mm. Then, it is pre-baked at 80 degrees Celsius for 1 hour, dried in a vacuum oven at 120 degrees Celsius for 6 hours, and treated at 180 degrees Celsius for 4 hours. Finally, it is hot-pressed at 280 degrees Celsius, with a pressure of 10 to 15 MPa and a holding time of 30 minutes. Step four: Composite metal reflective layer. A 0.5 mm thick aluminum alloy sheet is used. The aluminum alloy sheet is grade 5052 and has a tensile strength of not less than 230 MPa. The surface of the aluminum alloy sheet undergoes chemical pretreatment, specifically: immersion in an alkaline degreasing solution at 60°C for 15 minutes to remove surface oil, followed by acid pickling in a 10% sulfuric acid solution at room temperature for 5 minutes to activate the surface, and finally chemical oxidation treatment in a chromic acid-phosphoric acid mixture for 10 minutes to form a micron-level roughened surface. The treated aluminum plate is thoroughly rinsed with deionized water and dried. The two-component epoxy structural adhesive is thoroughly mixed and then uniformly coated onto the surface of the aluminum plate using a scraping method. The mass ratio of the main component to the curing agent of the two-component epoxy structural adhesive is 100:30, and the coating thickness is controlled between 0.15 and 0.20 mm. The coated aluminum plate is then bonded to the surface of the broadband absorption layer obtained in step three and rolled in a roller press with a pressure of 0.5 MPa to remove air bubbles. It is then pre-cured at 60 degrees Celsius for 4 hours and cured at 120 degrees Celsius for 6 hours. Step 5: Prepare the carbon fiber reinforced protective layer using a vacuum-assisted resin transfer molding process. Select a plain weave carbon fiber fabric with a specification of 3K and an areal density of 200 g / m². After cutting to the required size, lay 3 to 4 layers on the surface of the metal reflective layer obtained in Step 4. Prepare an epoxy resin system including 100 parts epoxy resin, 10 to 15 parts low-viscosity reactive diluent, 30 parts polyamide curing agent, and 0.5 parts defoamer. Place the composite material in a vacuum bag and introduce the resin system into the carbon fiber fabric under a vacuum of -0.09 to -0.095 MPa to fully impregnate it. After resin infusion, maintain the temperature at 60 degrees Celsius for 2 hours to allow the resin to initially gel, then cure at 120 degrees Celsius for 4 hours and then at 150 degrees Celsius for 2 hours. Step six, post-processing of the overall composite material: The prepared five-layer composite material is trimmed on a CNC milling machine to ensure dimensional accuracy and edge flatness. Then, stress relaxation treatment is carried out at 150 degrees Celsius for 4 hours to eliminate the internal stress generated during the preparation process. Finally, a polyurethane protective coating with a thickness of 50 to 80 micrometers is sprayed on the surface of the composite material.

7. The preparation method according to claim 6, characterized in that, In the preparation of the high magnetic permeability absorption layer substrate in step one, the epoxy resin and polyamide curing agent must be mixed and poured within 15 minutes to avoid excessive increase in the viscosity of the resin system affecting the laying quality. In addition, during the vacuum degassing process, it is necessary to ensure that the volume fraction of air bubbles in the mixture is reduced to below 0.5%.

8. The preparation method according to claim 6, characterized in that, In the preparation of the impedance transition layer described in step two, the dispersion of silicon carbide whiskers and flake carbonyl iron powder in the polyimide solution must ensure the uniformity of the filler dispersion in the matrix. Specifically, the dispersion is checked by optical microscopy to ensure that there are no agglomerates larger than 50 micrometers. The heating rate during the programmed heat treatment process is strictly controlled at 2 to 3 degrees Celsius per minute to ensure that the solvent evaporates fully and the polyimide is fully imidized.

9. The preparation method according to claim 6, characterized in that, In the preparation of the broadband absorption layer described in step three, the addition rate of the dispersion of functionalized multi-walled carbon nanotubes, graphene nanosheets and manganese zinc ferrite nanoparticles to the polyether ether ketone solution should be controlled at 5 to 10 ml per minute to avoid local precipitation of polyether ether ketone. In addition, a programmed pressurization method should be adopted during the hot pressing process. First, the material should be initially compacted at a pressure of 5 MPa for 5 minutes, and then the pressure should be increased to 10 to 15 MPa and maintained for 30 minutes.

10. The preparation method according to claim 6, characterized in that, In the chemical pretreatment process of the aluminum alloy sheet surface described in step four, the main components of the alkaline degreasing solution are aqueous solutions of sodium hydroxide and sodium silicate. The mass ratio of chromic acid to phosphoric acid in the chromic acid-phosphoric acid mixture is 2:

1. The surface roughness of the aluminum sheet after chemical oxidation treatment needs to reach 0.4 to 0.8 micrometers to ensure that the bonding strength with the epoxy structural adhesive is not less than 18 MPa. After applying the adhesive, the bonding and rolling operations need to be completed within 30 minutes to ensure the fluidity and wetting effect of the adhesive layer.

Citation Information

Patent Citations

  • Wear-resistant light unmanned aerial vehicle shell composite metal material

    CN118124213A

  • Broadband multi-layer structured wave absorbing composite material and preparation thereof

    CN101434134A

  • Method for synthesizing multi-layer impedance gradient composite electromagnetic shielding material by regulating impedance matching characteristics

    CN116904069A

  • Low-permeability carbonyl iron powder as well as preparation method and application thereof

    CN117976395A

  • Anti-electromagnetic interference high-frequency lightweight nano new material

    CN119798956A